2012
DOI: 10.1371/journal.pone.0028568
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Screen for G1/S Checkpoint Activators Identifies a Selective Activator of EIF2AK3/PERK Signalling

Abstract: Human cancers often contain genetic alterations that disable G1/S checkpoint control and loss of this checkpoint is thought to critically contribute to cancer generation by permitting inappropriate proliferation and distorting fate-driven cell cycle exit. The identification of cell permeable small molecules that activate the G1/S checkpoint may therefore represent a broadly applicable and clinically effective strategy for the treatment of cancer. Here we describe the identification of several novel small molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 54 publications
0
76
0
Order By: Relevance
“…1A, marked with a diamond). At least one of the proteins that did not recover was the short-lived cyclin D1 protein, whose translation has been shown to be blocked by eIF2a-dependent translational repression (Brewer and Diehl, 2000;Stockwell et al, 2012). Indeed, in our experiments cyclin D1 protein levels began decreasing within 0.5 hours of thapsigargin treatment and were undetectable by 2 hours (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…1A, marked with a diamond). At least one of the proteins that did not recover was the short-lived cyclin D1 protein, whose translation has been shown to be blocked by eIF2a-dependent translational repression (Brewer and Diehl, 2000;Stockwell et al, 2012). Indeed, in our experiments cyclin D1 protein levels began decreasing within 0.5 hours of thapsigargin treatment and were undetectable by 2 hours (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…ER stress has been reported to induce apoptosis in various cell types via the upregulation of protein translation mediated through the PERK-eIF2α pathway (24)(25)(26)(27). For instance, upon ER stress, the ER chaperone GRP78 dissociates from the PERK and initiates transphosphorylation with subsequent activation of the kinase (28).…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, the prolonged inactivation of eIF2-α result in reduced viability because of the loss of anti-apoptotic proteins, which are required for the survival of cancer cells (Fritsch et al 2007). Theoretically, a small molecule that could induce the phosphorylation of eIF2-α could sensitize cancer cells to paclitaxel (Stockwell et al 2012). In contrast to a previous cancer study (Lee do et al 2010), activation of PERK, which is a kinase upstream of eIF2-α, was shown to be beneficial in beta-amyloid-induced murine models of neurotoxicity.…”
Section: Discussionmentioning
confidence: 87%
“…The densitometric analysis results from western blotting are presented at the right panel. The bar means ± SD (n = 3; *p < 0.05; **p < 0.01) eIF2-α activity (Stockwell et al 2012). When CSM14.1 cells were incubated with AMC compounds, Cyclin D1 protein expression was downregulated in a dose-dependent manner within 4 h of compound exposure.…”
Section: Cap-dependent Translation Can Be Suppressed By Amc Compoundsmentioning
confidence: 99%